Optimal Capacitor Placement in Primary Distribution System Using Load Profile Consideration - ชูสกุล ณฐพล; ทามแก้ว พงษ์ศักดิ์; เกิดชื่น กาณฑ์ (RMUTL Engineering Journal, 2019)
This paper proposes the optimal capacitor placement in primary distribution power systems using multi- objective optimization called Non-dominated Sorting Genetic Algorithm, NSGA-II. The energy loss and average voltage deviation are included in the objective function. The load of distribution power systems are considered in three different settings: department store, factory and residential area, all installed in a 33- bus test system. These three load profiles are considered at peak load, average load, daily load divided in three durations, and real daily load. The results show that the compromise between system energy loss and voltage profile can be reached in average load.